Consumers’ perception of piped water supply and their willingness to pay for improved water supply: evidence from an Eastern Indian state - Tapasi Mohanty; Himanshu Sekhar Rout (Water Supply, 2024)
The objectives of the study are to analyse the perception of consumers on piped water supply, the consumers’ willingness to pay for improved water supply, and the factors that affect it. The sample unit is the consumer household of the public health divisions. The sample size is 181. A multistage random sampling procedure was adopted to choose the sample household. Descriptive statistics and structural equation models are used to analyse the data. This study found that consumer satisfaction is influenced by water supply quantity, pressure, timing, and visual aspects. The main factors causing interruptions include pipeline breakage, cyclone impact, summer water depletion, construction work, motor damage, and reservoir cleaning. Households are not well-informed about advance payment, its benefits, and the proper procedure for obtaining a receipt. Household income, education, satisfaction with water quality, the period of the service association, supply water price, and sufficiency of water during summer directly affect consumers’ willingness to pay. Discontent with appearance and taste affects quality dissatisfaction and indirectly willingness to pay. HIGHLIGHTS 83.7% of households stated that they were facing an interruption of the water service. The main factors causing interruptions include pipeline breakage, cyclone impact, summer water depletion, construction work, motor damage, and reservoir cleaning.; Household income, education, satisfaction with water quality, supply water price, and sufficiency of water during summer directly affect consumers’ willingness to pay.;